Body size affects host defensive behavior and progeny fitness in a parasitoid wasp, Lysiphlebus fabarum. Issue 3 (24th January 2014) - Ameri, Mohammad; Rasekh, Arash; Michaud, J.P.
Abstract This study tested effects of maternal body size on foraging behavior and progeny development in a thelytokous population of Lysiphlebus fabarum (Marshall) (Hymenoptera: Braconidae). Small and large wasps were reared from first and second instar hosts [black bean aphid, Aphis fabae Scopoli (Hemiptera: Aphididae)], respectively, and each was provided with a patch (bean leaf disk) containing either 15 small (second instar) or 15 large (fourth instar) hosts for a 30‐min foraging period. Neither body size nor host size affected time allocation to various behaviors within a patch, but second instar aphids produced significantly more mummies than fourth instars. The preferred attack orientation was from the side of the aphid, suggesting wasps were sensitive to the risk of smearing with cornicle secretions. Few wasps developed in fourth instar hosts, suggesting later host instars were somewhat resistant to parasitism. Second instar hosts, the most suitable stage for L. fabarum development, relied more on defensive behavior, specifically kicking and secreting cornicle droplets. Large wasps were more likely to elicit a double cornicle secretion, indicating that aphids graded their response to the size of the attacker. Larger wasps were also more likely to be smeared with cornicle secretion, suggesting they were more vulnerable than small wasps. Although small wasps had smaller eggs than large wasps, there was no effect of maternal egg size on the size of progeny. However, daughters of small females emerged with larger egg loads than daughters of large mothers, and their eggs tended to be slightly smaller, although not significantly. Regression analysis revealed a positive correlation between maternal egg size and progeny developmental time for small and large wasps, and between maternal egg size and progeny egg load for small wasps. These results confirm maternal effects of body size in an aphid parasitoid, and reveal that vulnerability to host behavioral defenses is also body size dependent.